Reuniting Codex Angus (GA L2378) with Its Lost Bifolium. - Jones, Hefin J. (TC: A Journal of Biblical Textual Criticism, 2025)
This article reports on the discovery and reuniting of a lost bifolium (the former GA L2386) with its parent gospel lectionary codex (GA L2378) and the consequent investigation into their cataloging and provenance. Using online databases and image sets, combined with information from provenance research by previous investigators, we were able to locate and compare the bifolium with its parent codex. Subsequently, further investigation and interpretation of older cataloging information for both items reinforced the connection of the reunited codex with the coerced removal of the Kosinitsa monastery library in 1917. It also increased our confidence in identifying GA L2378 with GA L1246, described by Kirsopp Lake in 1902 and registered by C. R. Gregory in his Liste in 1908. This article illustrates the possibilities and value of applied fragmentology not only for updating the Liste, but also for increasing our knowledge of the provenance of dispersed manuscripts.